International correlation risk - Mueller, Philippe; Stathopoulos, Andreas; Vedolin, Andrea (Journal of Financial Economics, 2017)
We show that the cross-sectional dispersion of conditional foreign exchange (FX) correlation is countercyclical and that currencies that perform badly (well) during periods of high dispersion yield high (low) average excess returns. We also find a negative cross-sectional association between average FX correlations and average option-implied FX correlation risk premiums. Our findings show that while investors in spot currency markets require a positive risk premium for exposure to high dispersion states, FX option prices are consistent with investors being compensated for the risk of low dispersion states. To address our empirical findings, we propose a no-arbitrage model that features unspanned FX correlation risk.